Status and analysis of undetected plague cases in Yunnan Province, China - Chao Su; Chao Su; Biao Duan; Qun Duan; Zhaokai He; Hanyu Sha; Yun Liang; Ennian Pu; Shuai Qin; Ran Duan; Dongyue Lyu; Wenbao Li; et al. (Frontiers Media S.A., 2024)
BackgroundThe virulence of Yersinia pestis strains in the Rattus flavipectus plague focus is relatively low. The purpose of this study was to investigate the undetected, sporadic plague cases in plague foci and provide the basis for plague prevention and control.MethodsA 3-year-old plague-confirmed case was investigated in the R. flavipectus plague focus of Yunnan Province in 2020 due to the intensive screening for fever symptoms during the coronavirus disease 2019 (COVID-19) pandemic. Epidemiological investigation, laboratory testing, and clinical treatment were conducted for the case. The expanded survey was carried out around the case within a 7-km radius, including the resident population, domesticated dogs, and rats. PCR and indirect hemagglutination tests were performed on the collected samples.ResultsThe isolation rates of Y. pestis were 100.0% (7 out of 7) in dead rats and 4.00% (3 out of 75) in live rats in the survey area of the foci. A total of 5.00% (6 out of 120) of the domesticated dogs were F1 antibody positive. Nine local people were determined for plague infection recently (0.92%, 9 out of 978). The locations of human cases coincided with the Y. pestis epidemic area among the animals.ConclusionThis study discovered the existence of plague cases that had not been detected by routine surveillance in the R. flavipectus plague focus, and the actual epidemic of human infection may be underestimated.